2022
DOI: 10.3389/fevo.2022.833129
|View full text |Cite
|
Sign up to set email alerts
|

Anthropause Opportunities: Experimental Perturbation of Road Traffic and the Potential Effects on Wildlife

Abstract: The SARS-CoV-2 pandemic severely reduced many human activities. So pronounced was the change, it has given rise to the term “anthropause”: the considerable alteration of modern human activities. Among these was surface transportation, with prolonged traffic reductions, in excess, of 50% in many countries. Roads and traffic are responsible for functionally fragmenting ecosystems, wildlife populations, and species interactions. The unintentional “dialing-down” of traffic has given continuous monitoring systems o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Travel restrictions during the pandemic hindered scientific research and fieldwork opportunities (Saraswat & Saraswat, 2020), but also provided opportunities (Bates et al, 2021;Perkins et al, 2022). By utilising an extensive database of citizen science roadkill records over an 8-year time series, and using compositional data analysis, a previously under-utilised method for relative abundance data, this study has revealed the impact that vehicles may have on…”
Section: Con Clus Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Travel restrictions during the pandemic hindered scientific research and fieldwork opportunities (Saraswat & Saraswat, 2020), but also provided opportunities (Bates et al, 2021;Perkins et al, 2022). By utilising an extensive database of citizen science roadkill records over an 8-year time series, and using compositional data analysis, a previously under-utilised method for relative abundance data, this study has revealed the impact that vehicles may have on…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…The reduction in human activity, especially with respect to transport (Du et al, 2021;Havaei-Ahary, 2021;Yasin et al, 2021), was so profound that a global 'quietening' was detected (Lecocq et al, 2020); a time period referred to as the 'anthropause' (Rutz et al, 2020). Such a reduction in traffic offers the equivalent of a unique perturbation experiment to allow us to assess road mortality risk according to species traits (Perkins et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For example, recreational use of beaches impacted piping plover (Charadrius melodus) demographics by lowering chick survival during weekends and in areas of intense use 78 . Roads, vehicle traffic and collisions also cause wildlife mortality 79 . Traffic reductions during early COVID-19 lockdowns in central Europe led to sharp decreases in road mortality in large mammals, such as roe deer, but increased collisions with badgers indicating heterogeneous effects on demographic responses across species 80 .…”
Section: Demographic Responsesmentioning
confidence: 99%
“…These dramatic abruptions in global human activity have created the greatest natural experiments of our time, allowing the robust assessment of anthropogenic effects on ecological systems ( Rutz et al, 2020 ). Notably, global lockdowns significantly decreased road traffic, with vehicle use dropping by over 50% in many countries ( Perkins et al, 2022 ). Recent work has shown that reduced vehicular traffic during the lockdowns has caused animals to shift their space use near roads and urban areas ( Benson et al, 2021 , Corradini et al, 2021 , Wilmers et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%